Phosphorus contents in the soil in function of the modes of application of phosphate fertilizer in two crops in succession - Marcos Merten, Gean; Sérgio Rabello de Oliveira, Paulo; Richart, Alfredo (Scientia Agraria Paranaensis, 2021)
Tropical soils are naturally poor in phosphorus and, due to the strong interaction with mineral constituents, the ways of applying phosphate fertilizers can increase the efficiency of absorption by crops. The objective of this analysis was to evaluate the distribution of P at different depths depending on the application of phosphate fertilizer in wheat and common bean crops grown in a Dystrophic Red Latosol from Toledo, western Paraná. The work was carried out under field conditions at the experimental unit of the Agronomy course at the Pontifical Catholic University of Paraná (PUCPR), Campus from Toledo. The block design was used in the case, in a scheme of sub-subdivided plots in the space, the first factor being the application mode, the second local factor (lines and between lines), and the third-factor sampling depth (0 – 5, 5 – 10, 10 – 15, 15 – 20 cm), and collections were carried out at seven points in each plot, in two consecutive years. The first soil collection was carried out after the wheat harvest, with soil samplings being performed to quantify the amount of P added to the soil. The soil samples were collected at seven points per plot, four between the lines and three in the sowing lines, in a straight line in each plot, the same procedure was performed after harvesting the bean crop and the second collection was carried out after the bean crop harvest, repeating the analyses, using the Mehlich-1 method. Phosphate fertilizer application modes did not influence P contents in the soil. The highest P contents were obtained at 0-5 cm depth, decreasing along the sampled depths.